The Use of Computers and Augmentative and Alternative Communication Devices by Children and Young With Cerebral Palsy. - Pousada Garcia, Thais; Pereira Loureiro, Javier; Groba Gonzalez, Betania; Nieto Riveiro, Laura; Pazos Sierra, Alejandro (Assistive Technology)
The purpose of the study was to determine the use of computers and assistive devices amongst children with cerebral palsy (CP) and establish the satisfaction level of both users and educational staff. The study was carried out with 30 children with cerebral palsy. A questionnaire was designed to characterize the use of new technologies and assistive devices. Some of the questions were reserved for the teachers. Even though 29 users show some type of communication difficulty, only 4 users dispose of a computer-aided communication device, with the static symbolic board being the most widely used device (4). More than half of the participants (17) regularly use a computer, 16 of them requiring some type of assistive device. The perception of the teachers with regard to the use of Information and Communications Technologies (ICTs) in the classrooms is positive in 5 out of 6 cases. ICTs only provide assistance if their application is accompanied by the involvement of professionals and the child's social environment. The low use of Augmentative and Alternative Communication techniques along with the absence of communication codes reveal the need to establish training protocols. The inclusion of social, physical, and personal factors is considered essential in order to evaluate the needs for assistive technology.